A novel rheometer design for yield stress fluids. Issue 4 (3rd January 2014) - Samaniuk, Joseph R.; Shay, Timothy W.; Root, Thatcher W.; Klingenberg, Daniel J.; Scott, C. Tim
<x xml:space="preserve">Abstract</x> An inexpensive, rapid method for measuring the rheological properties of yield stress fluids is described and tested. The method uses an auger that does not rotate during measurements, and avoids material and instrument‐related difficulties, for example, wall slip and the presence of large particles, associated with yield stress fluids. The method can be used for many types of yield stress fluids, including concentrated lignocellulosic biomass. Sample preparation prior to measurement is minimal, reducing, or eliminating disruption of the sample. We show that measurements using this technique compare well with measurements obtained with a vane rheometer. A variation of the described method is proposed that would make it easier to measure time‐dependent rheological properties. © 2014 American Institute of Chemical Engineers AIChE J, 60: 1523–1528, 2014